Unusual galactic H II regions at the intersection of the central molecular zone and the far dust lane - Anderson, Loren Dean; Sormani, Mattia C.; Glover, Simon (The astrophysical journal, 2020)
Sgr E is a massive star formation complex found toward the Galactic center that consists of numerous discrete, compact H ii regions. It is located at the intersection between the central molecular zone (CMZ) and the far dust lane of the Galactic bar, similar to “hot spots” seen in external galaxies. Compared with other Galactic star formation complexes, the Sgr E complex is unusual because its H ii regions all have similar radio luminosities and angular extents, and they are deficient in ∼10 μm emission from their photodissociation regions (PDRs). Our Green Bank Telescope radio recombination line observations increase the known membership of Sgr E to 19 H ii regions. There are 43 additional H ii region candidates in the direction of Sgr E, 26 of which are detected for the first time here using MeerKAT 1.28 data. Therefore, the true H ii region population of Sgr E may number >60. Using APEX SEDIGISM 13CO data we discover a 3.0 × 105 molecular cloud associated with Sgr E, but find few molecular or far-infrared concentrations at the locations of the Sgr E H ii regions. Comparison with simulations and an analysis of its radio continuum properties indicate that Sgr E formed upstream in the far dust lane of the Galactic bar a few million years ago and will overshoot the CMZ, crashing into the near dust lane. We propose that the unusual infrared properties of the Sgr E H ii regions are caused by their orbits about the Galactic center, which have possibly stripped their PDRs.
Gesehen am 22.10.2021